Xeno-free culture of human pluripotent stem cells on oligopeptide-grafted hydrogels with various molecular designs - Chen, Yen-Ming; Chen, Li-Hua; Li, Meng-Pei; Li, Hsing-Fen; Higuchi, Akon; Kumar, S. Suresh; Ling, Qing-Dong; Alarfaj, Abdullah A.; Munusamy, Murugan A.; Chang, Yung; Benelli, Giovanni; Murugan, Kadarkarai; et al. (Nature Publishing Group, 2017)
Establishing cultures of human embryonic (ES) and induced pluripotent (iPS) stem cells in xeno-free conditions is essential for producing clinical-grade cells. Development of cell culture biomaterials for human ES and iPS cells is critical for this purpose. We designed several structures of oligopeptide-grafted poly (vinyl alcohol-co-itaconic acid) hydrogels with optimal elasticity, and prepared them in formations of single chain, single chain with joint segment, dual chain with joint segment, and branched-type chain. Oligopeptide sequences were selected from integrin- and glycosaminoglycan-binding domains of the extracellular matrix. The hydrogels grafted with vitronectin-derived oligopeptides having a joint segment or a dual chain, which has a storage modulus of 25 kPa, supported the long-term culture of human ES and iPS cells for over 10 passages. The dual chain and/or joint segment with cell adhesion molecules on the hydrogels facilitated the proliferation and pluripotency of human ES and iPS cells.